Deeb, Lara, An Enchanted Modern: Gender and Public Piety in Shi'i Lebanon, Princeton, Princeton University Press, 2006, 275 pp. - Pastor, Camila (Estudios de Asia y África, 2009)
Deeb, Lara, An Enchanted Modern: Gender and Public Piety in Shi'i Lebanon, Princeton, Princeton University Press, 2006, 275 pp.